Monitoring Detrusor Oxygenation and Hemodynamics Noninvasively during Dysfunctional Voiding - Andrew J. Macnab; Lynn S. Stothers; Babak Shadgan (Advances in Urology)
The current literature indicates that lower urinary tract symptoms (LUTSs) related to benign prostatic hyperplasia (BPH) have a heterogeneous pathophysiology. Pressure flow studies (UDSs) remain the gold standard evaluation methodology for such patients. However, as the function of the detrusor muscle depends on its vasculature and perfusion, the underlying causes of LUTS likely include abnormalities of detrusor oxygenation and hemodynamics, and available treatment options include agents thought to act on the detrusor smooth muscle and/or vasculature. Hence, near infrared spectroscopy (NIRS), an established optical methodology for monitoring changes in tissue oxygenation and hemodynamics, has relevance as a means of expanding knowledge related to the pathophysiology of BPH and potential treatment options. This methodological report describes how to conduct simultaneous NIRS monitoring of detrusor oxygenation and hemodynamics during UDS, outlines the clinical implications and practical applications of NIRS, explains the principles of physiologic interpretation of NIRS voiding data, and proposes an exploratory hypothesis that the pathophysiological causes underlying LUTS include detrusor dysfunction due to an abnormal hemodynamic response or the onset of oxygen debt during voiding.